Meja Makan Pelbagai Fungsi diinspirasikan oleh Bonet Kereta - Sze Jie, Ang; Selimin, Mohamad Ali (Research in Management of Technology and Business, 2021)
Multipurpose furniture provides more than one function and leads to many advantages such as reduce the quantity of furniture usage and purchasing cost-wise. Small-sized housing owner needs to reduce the amount of furniture in order to have freer floor space for other purposes or give comforts to all. Therefore, the aims of this study are to design and fabricate a prototype of a multipurpose dining table inspired by a car bonnet. This study can be clustered into three main phases namely research survey, design development, and prototype fabrication. The research survey was conducted using a questionnaire to determine the design criteria of the dining table. Meanwhile, the design development phase includes ideation, idea development, and final design selection. The prototype fabrication starts with mock-up development followed by technical drawing and ends with the prototype fabrication process. This study found that the majority of the respondents preferred a dining table with a rectangular top table design, the original wood color as finishing, and favour on modern design. The final design of this study embraced the design criteria obtained from the questionnaire that fit up to 4 peoples. The storage space is also large enough to store kitchen items. The results of this study are significant for the small to medium-sized homes to provide freer floor space to the user.